Activating Tax Inventory Procedures and Their Role in Increasing Tax Revenues: Applied research in the General Authority for Taxation (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to shed light on the tax inventory procedures and how to activate them to address the phenomenon of low tax revenue in its dimensions (activating field survey methods, information provided by supporting authorities, as well as coordination between income and real estate taxes) to increase tax revenues, as the General Tax Authority did not implement some of the procedures Tax procedures, such as field survey procedures, which stopped working with this procedure in Iraq since 2000 by applying the experience of self-assessment and was only done at the beginning of 2014 after this procedure was stopped, as well as the experience of coordination between income and real estate taxes was applied only for a relatively short period from 1998 to 2002 Also, the information that will be obtained from the supporting authorities will have a major role in reducing tax evasion and complying with income tax, so the aim of the research will be to shed light on the activation of tax inventory procedures to reduce the evasion of income taxpayers and achieve an increase in tax revenues, whenever possible The authority adopts new concepts to activate the tax inventory procedures whenever it is reflected on their tax performance in attracting new taxpayers. To achieve this, the research relied in analyzing its variables on the questionnaire as a main tool for collecting data and information, from the sample of (76) general managers, directors of departments and unit officials, and the answers were analyzed by relying on the statistical program (SPSS). Taxes increase tax revenues, and this is a good indicator of the effect of tax inventory procedures on the performance of the research sample.